Pelaksanan Pentingnya Proses Upaya Mediasi untuk Tindak Pidana Ringan di Desa Merangin - Prayudi Saputra, Rian (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Merangin Village is one of the villages included in the Kuok District area which was previously called West Bangkinang District with an area of 10,037 Ha. Which initially consisted of five hamlets, including Dusun Pulau Terap II, Dusun Pulau Terap Tengah, Dusun Pulau Terap I, Dusun Lereng, and Dusun Rantau Berangin. Merangin was expanded, for the smooth running of government in this village. A criminal act can be defined as an act which, if violated, will result in clear sanctions and in accordance with the Criminal Code. The presence of criminal law in society is intended to provide a sense of security to individuals and groups of society in carrying out their daily activities. Criminal cases arise because there is a criminal act that is handled by law enforcement. Criminal cases always arise whenever there is a criminal process. Criminal acts or crimes are an inseparable part of life in society. One of the criminal cases that often occurs in society is criminal acts that have value or are light and not dangerous, namely petty theft.